The Effect of 6-Thioguanine on Alternative Splicing and Antisense-Mediated Exon Skipping Treatment for Duchenne Muscular Dystrophy - Verhaart, Ingrid E. C. (Public Library of Science, 2012)
The severe muscle wasting disorder Duchenne muscular dystrophy (DMD) is caused by genetic defects in the DMD gene, leading to a complete absence of dystrophin protein. Of the therapeutic approaches addressing the underlying genetic defect, exon skipping through antisense oligonucleotides (AONs) is the closest to clinical application. Several strategies to improve the efficiency of this approach are currently being investigated, such as the use of small chemical compounds that improve AONmediated exon skipping levels. Recently, enhanced exon skipping in combination with a guanine analogue, 6-thioguanine (6TG) was reported for phosphorodiamidate morpholino oligomers (PMO). Here the effect of 6TG on the exon skipping efficacy of 2’-O-methyl phosphorothioate RNA (2OMePS) and PMO AONs in vitro and in vivo was further evaluated, as well as the effect of 6TG by itself. Results confirm an increase of exon skipping levels in vitro, however, in contrast to the previous report, no effect was observed in vivo. Importantly, 6TG treatment in vitro resulted in numerous additional DMD exon skipping events. This, in combination with the known cytotoxic effects of 6TG after incorporation in DNA, warrants reconsidering of the use of 6TG as enhancer of AON efficiency in DMD, were chronic treatment will be required.